1961
DOI: 10.1126/science.134.3474.279
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles hackeri , a Vector of Plasmodium knowlesi in Malaya

Abstract: Anopheles hackeri, a mosquito commonly found breeding in nipa palm leaf bases along the Malayan coast, was demonstrated to be infected with Plasmodium knowlesi by the inoculation of sporozoites into an uninfected rhesus monkey. This was the first demonstration of a natural vector of any monkey malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
2

Year Published

1977
1977
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 3 publications
2
57
0
2
Order By: Relevance
“…Adults were found resting during the day on the base of Nipa palms and close to houses but apparently they do not bite humans and domestic animals (Reid et al 1952;Wharton & Eyles 1961;Wharton et al 1964;. They were also collected using monkey traps on the ground and on a platform 4.5 m above ground (Reid et al 1952).…”
Section: Anopheles (Cellia) Hackerimentioning
confidence: 99%
See 1 more Smart Citation
“…Adults were found resting during the day on the base of Nipa palms and close to houses but apparently they do not bite humans and domestic animals (Reid et al 1952;Wharton & Eyles 1961;Wharton et al 1964;. They were also collected using monkey traps on the ground and on a platform 4.5 m above ground (Reid et al 1952).…”
Section: Anopheles (Cellia) Hackerimentioning
confidence: 99%
“…They were also collected using monkey traps on the ground and on a platform 4.5 m above ground (Reid et al 1952). They fed predominantly on monkeys (Reid & Weitz 1961) and prefer to feed in the canopy of mangrove forests (Wharton & Eyles 1961;Wharton et al 1964). Adults were also caught on human-baited net trap at ground level (Wharton & Eyles 1961).…”
Section: Anopheles (Cellia) Hackerimentioning
confidence: 99%
“…1). The first vector found in nature to be infected with P. knowlesi was A. hackeri, a predominantly zoophilic mosquito, in Selangor State, Peninsular Malaysia, in 1961 (79). Experimental studies in the United States undertaken in the 1960s with the H strain of P. knowlesi (isolated from the American surveyor) showed that among the anophelines tested for the presence of sporozoites in the salivary glands and their capability of transmitting P. knowlesi to rhesus macaques, A. balabacensis was the most competent vector, followed by A. stephensi, A. maculatus, and A. freeborni (80,81).…”
Section: Vectorsmentioning
confidence: 99%
“…Anopheles hackeri se identificó como el vector más importante de P. knowlesi (37), A. balabacencis introlatus, como el vector de P. cynomolgi (38), y A. leucosphyrus como el de P. inui (39), plasmodios causantes de malaria en simios. Sin embargo, se ha observado que A. hackeri es poco atraído por los humanos (34,37), mientras que A. b. introlatus y A. leucosphyrus tienen gran afinidad por los simios y humanos (39), y se ha establecido que esta última especie actúa como vector de P. knowlesi para ambos huéspedes, por lo que podría estar implicada en su transmisión a humanos. Otro candidato a vector de malaria como zoonosis, es Anopheles b. balabacensis, reconocido transmisor de malaria humana y de P. cynomolgi y P. inui (40).…”
Section: Huéspedes Y Vectores Naturalesunclassified